2016
DOI: 10.1007/s00343-016-5027-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Three Gorges Dam on the spawning stock and natural reproduction of Chinese sturgeon in Changjiang River, China

Abstract: Chinese sturgeon ( Acipenser sinensis ) is the fl agship species of the Changjiang River. The migration route of this species is blocked by the fi rst dam, the Gezhou Dam, and its reproduction is aff ected by the Three Gorges Dam (TGD), one of the largest dams in the world. We studied the impact of the impoundment of the Three Gorges Reservoir (TGR) since 2003 on the spawning stock and the natural reproduction of the Chinese sturgeon by using our monitoring data from 1997 to 2013. Results indicate that TGR imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The hydro‐environment required by Chinese sturgeon has also been dramatically influenced (Gao, Lin, Li, Duan, & Liu, ; Wang & Xia, ; Zhang, Yang, Wei, Du, & Wang, ; Zhang et al, ), resulting in reduction of spawning ground. Flow regime alterations caused by the TGD operation have greatly decreased median monthly flows during the spawning season, especial in October (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The hydro‐environment required by Chinese sturgeon has also been dramatically influenced (Gao, Lin, Li, Duan, & Liu, ; Wang & Xia, ; Zhang, Yang, Wei, Du, & Wang, ; Zhang et al, ), resulting in reduction of spawning ground. Flow regime alterations caused by the TGD operation have greatly decreased median monthly flows during the spawning season, especial in October (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In the past, a The acoustic identification method of Chinese sturgeon from echograms should be improved. Currently, the main ground for the identification is that the adult Chinese sturgeon is large, thus its TS should be stronger than the TS values of common river fishes [17][18][19][20][21][22]. In fact, other large body fishes in the Yangtze River, such as the four major Chinese carps, can grow up to 131.1 cm in body length [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only the hydroacoustic methods seem to be applicable to survey and study the adult population of Chinese sturgeon in the Yangtze River. On the other hand, future hydroacoustic surveys should not only be constructed in a zigzag mobile survey [17][18][19][20][21][22] or a stationary point survey [37], but also long-time fixed cross section monitoring is highly recommended. As the fish is a migrating species, fixed cross section monitoring in its migration route could be highly efficient with low cost [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the optimal water temperature for spawning is 16–20 °C (Wei, ). Since the impoundment of the Three Gorges Reservoir (TGR) in 2003, the spawning dates of the Chinese sturgeon have been delayed 30–40 days because of the “temperature hysteresis effect” (Gao, Lin, Li, Duan, & Liu, ). In 2013, there was no evidence that the Chinese sturgeon had spawned below the GD.…”
Section: Introductionmentioning
confidence: 99%